Reconstructing a fractured indigenous knowledge system - Jimoh, Anselm Kole (Array, 2019)
African colonial experience bequeathed a culture of epistemological silencing of African indigenous epistemology with its monochrome logic of Western epistemology. It systematically devalued African indigenous knowledge systems by presenting African intellectual enterprise as alogical and sometimes primitive. Immediately after the colonial experience, the attempts by some African scholars to establish the depth of African scholarship fractured the African knowledge systems. This is because they attempted to use Western logic and models as paradigms in investigating, interrogating, and evaluating our knowledge practice. In this paper, I argue for the need to reconstruct fractured African indigenous epistemology. I shall present how African indigenous knowledge systems (AIKS), otherwise referred to in the paper as African indigenous epistemology, are distorted and fractured. After that, I shall propose its reconstruction by articulating how we acquire and validate knowledge in African indigenous epistemology. By African indigenous epistemology, I mean a system of investigating, understanding, assimilating, and attributing African conception of reality that is distinctively African and philosophical. To this end, I shall adopt the philosophical methodology of critical analysis, evaluation, and reconstruction to delineate the notions of indigenous knowledge systems (IKS), African indigenous epistemology, the fracturing effect of colonialism, globalisation, and Western framework on African indigenous knowledge systems (AIKS). I conclude that to reconstruct African indigenous epistemology, we have to free it from the grip of Western evaluative paradigms.